Marketing Strategy of Allisya Protection Plus at Allianz STAG Genteng Biru: Islamic Economic Perspective - Irmayani, Ni Wayan Dian; Sudiarsa, I Gede (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research is motivated by the lack of awareness of the Indonesian people about the importance of insurance in future life. Therefore, a strong strategy is needed from the agents to market insurance to the public and to survive to develop the company, especially Allianz Insurance and Allianz STAG Blue Tile partners. This study is a field study using descriptive qualitative methods with research subjects consisting of core subjects and supporting subjects, namely Business Partners, business executives and allisya Protection Plus customers. The results of this study indicate that the marketing strategy of allisya Protection Plus Insurance at Allianz STAG Genteng Biru partners carried out by agents is as follows: segmentation, Target market, positioning, marketing tactics, differentiation, marketing mix, Sales, Marketing Value, brand, Service and process. The purpose of this study is to evaluate and understand the marketing strategy of Allisya Protection Plus Insurance at Allianz STAG Blue Tile partners. This study also aims to determine how the marketing strategy of Allisya Protection Plus Insurance according to the perspective of Islamic Economics. Allisya Protection Plus Insurance Marketing Strategy at Allianz STAG Genteng Biru Partners is carried out by agents by paying attention to several aspects, such as segmentation, targeting, positioning, marketing tactics, differentiation, marketing mix, Sales, Marketing Value, brand, service, and process. In addition, this marketing strategy is also explained in the context of Islamic Economics, where agents try to market products in accordance with Sharia principles and provide good service to prospective customers.